Report on UNITA/WAIFEM joint workshop on multilateral debt negotiation - West African Institute for Financial and Economic Management (WAIFEM) (Lagos : West African Institute for Financial and Economic Management (WAIFEM), 1998)
The workshop was in two parts. Part 1 dealt with the theory of negotiation being a synthesis of best practices in negotiations compiled by experienced researchers. Part 2 concerned the application of the theoretical literature to multilateral debt negotiations.
Includes bibliographical references.
osc 27/07/2016, rpm 05/09/2016
Loans
Keywords: Debt Management; Debt negotiation; Nigeria